Уровень экономической информированности старшеклассников средних школ - Денисова, Е. (Социология: теория, методы, маркетинг, 2007)
The paper analyzes empirical data relative to the economic competency among the senior pupils of secondary school and aimed at determining the level of economic knowledge. Moreover, subjective and objective factors contributing to the adequate knowledge acquisition are characterized.